Web transcript verification using check digit as secure number - Abd Halim, Muhamad Rais; Mahdin, Hairulnizam; Yaacob, Siti Salwani (Faculty of Electronic and Computer Engineering (FKEKK), Universiti Teknikal Malaysia Melaka (UTeM), 2017)
The case of fraudulent on academic qualification document is increasing due to the advancement of editing technology. This makes document forgery easy to be done. It has becoming a worldwide problem to verify the academic documents including the degree’s certificate and academic transcript. It is frightening situation when people without the right qualification working as professional in the area that will harm the society. Manual verification can be time consuming and not practical to be implemented. Therefore, it is paramount to have a web-based solution that can function all day long to perform this task. In this paper, dual check digit approach is proposed to verify the authenticity of an academic transcript. Three check digit methods which are Universal Product Code Mod 10 (UPC Mod 10), International Standard Book Number (ISBN Mod 11), and Luhn Mod 10 have been applied to test their reliability in carrying this task. The simulation results show that the combination of ISBN-11 and UPC Mod 10 performed very well to validate the authenticity of the transcripts.